Dynamic changes in the transcriptome of tropical region-originated king grasses in response to cold stress - Lai, Xianjun; Yan, Junfeng; Chen, Zihan; Zhang, Yizheng; Luo, Fan; Cai, Guangze; Yan, Lang (Frontiers in Plant Science, 2025)
IntroductionCold acclimatization in tropical region-originated plants involves complex gene expression reprogramming to adapt to fluctuating temperatures. However, the molecular mechanisms and gene networks regulating cold tolerance in king grass remain largely unknown.MethodsTo address this, we established a full-length reference transcriptome of king grass to enhance assembly quality and performed multiple time-point transcriptomic analyses following cold treatment at 4°C. Differentially expressed genes (DEGs) and transcription factors (TFs) involved in cold stress response were identified and analyzed through clustering and co-expression network analysis.ResultsA total of 13,056 DEGs were identified and classified into nine clusters via k-means analysis. The cold response exhibited three distinct phases: early (before 3 h), middle (6–24 h), and late (48–72 h). Early-responsive genes were enriched in glycolipid metabolism and photosynthesis, middle-stage genes in carbohydrate metabolism, and late-stage genes in cold stress, osmotic stress, and endogenous stimuli responses. Key regulators of the ICE-CBF-COR signaling module, including 13 positive and negative regulators, were identified. The co-expression network further revealed mutual regulatory interactions within this module, highlighting its role in cold stress adaptation.DiscussionOur findings provide insights into the cold tolerance mechanisms of king grass, offering a genetic basis for modifying cold stress regulators. This research contributes to the broader understanding of low-temperature adaptive mechanisms in tropical plants and supports future breeding strategies for improved cold tolerance.